Pelatihan Pembuatan Media Pembelajaran Berbasis Canva untuk Menstimulasi Keterampilan Berbahasa pada Guru YPI Bahrul Ulum I Bulu Balen Bojonegoro - Anisah, Giati; Kusna, Siti Labiba; Puspitasari, Endang (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Educational institutions need to adapt to the development of the world of technology which is accelerating very quickly, both in the development of learning, learning innovation, and the fulfillment of facilities and infrastructure as well as to improve their quality. One of the uses of technology in education is to support learning. The purpose of this activity is to provide knowledge to teachers by utilizing the Canva application as a creative and innovative learning medium for language learning in children. The training method is by providing material as a basis for initial knowledge, explaining the use of the Canva application in learning and tutorials for making learning videos. The results of the activities of the participants were very active and enthusiastic about participating in the activity. The conclusion of the activity is continued for the development of material and content of learning media to stimulate children's language.